Construction of a composite measure describing the quality of the environment in Poland - Frodyma, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The concept of sustainable development is a hot and widely discussed issue. In this paper we will discuss only one aspect of sustainable development, namely environmental sustainability. Environmental sustainability is understood as a target state in a positive environment which is claimed by the rational economy of natural resources and outlays for environmental protection. Environmental sustainability assessment involves the construction of suitable metrics. The purpose of this paper is the construction of a composite measure that describes the state of the environment, in particular voivodships in Poland. Composite measure, describing the state of the environment and measures of sub-composite related to the specific domain of environmental sustainability, will be built based on selected indicators presented in “a shortlist of regional indicators” developed by the team of T. Borys (Borys (ed.), 2005). For the construction of composite measures, two different indicators of development will be applied. The arithmetic mean is used as an example of a linear measure. As regards a non-linear measure, we selected a development pattern method. We used these two methods to rank Polish voivodships in terms of the state of their natural environment. Subsequently, these composite measures were compared.
Mathematical Economics, 2012, Nr 8 (15), s. 29-44
Keywords: composite measure; environmental sustainability; arithmetic mean; development pattern method